Implementasi Program Penyediaan Air Bersih Di Daerah Perkotaan - M. Hadi; Sujianto '; Chalid Sahuri (Universitas Riau, 2012)
This study aims to determinethe factors that affect the implementation of the Clean Water Program in the Dumai City. This studyused a qualitative descriptive approach where research procedures generate descriptive data in theform of words written or spoken of the people or actors can be observed. The results indicate theimplementation of the Clean Water Program in Dumai City can not be done well is influenced byseveral factors, namely clarity of purpose and the level of consensus among the executive inachieving these objectives, the type of factors that stand to benefit and unlimited clients, katakteristikexecutor and social factors economic and political.